Indirect and moderated effects of parent-child communication on drinking outcomes in the transition to college. (March 2019) - Hartman, Jessica D.; Corbin, William R.; Curlee, Alexandria S.; Fromme, Kim
Graphical abstract: Unlabelled Image Highlights: Effects of parental communication depend on levels of parental monitoring. High parental communication with low monitoring related to more binge drinking. High parental communication with high monitoring linked to less permissive values. Less permissive drinking values related to lower levels of binge drinking. Drinking values mediate relations between parental behaviors and binge drinking.